Evaluation of pre-germinative treatments in seeds of Cereus jamacaru DC subsp. jamacaru (Cactaceae) (Research, Society and Development, 2020)
Cereus jamacaru DC subsp. jamacaru (mandacaru) is an endemic species in Brazil belonging to Cactaceae of great ecological importance, as it is a pioneer in the colonization of arid and inhospitable environments, and contributes directly to the food chain for its fruits highly appreciated by fauna. Therefore, this work aimed to evaluate, through chemical scarification, the germinative behavior of C. jamacaru subsp. jamacaru. The cactus seeds were collected in May 2016 in the city of Quixelô-CE-Brazil. The acids used in chemical scarification were acetic acid, hydrochloric acid, propionic acid and sulfuric acid for 5, 10 and 15 minutes. The seeds were placed in Petri dishes, and placed to germinate in a B.O.D. with a light/dark cycle of 12 hrs at 30 ºC. Daily readings were performed and analyzed: percentage of germination, Germination Speed ​​Index (GSI) and mean germination time (Tm). The results indicate that acids negatively interfere in seed germination when compared to the control group, mainly acetic and propionic acid, since at the end of the experiment only 8% of the seeds germinated when subjected to acetic acid, and 4% to the propionic. In addition, there was also a significant increase in Tm. Thus, water is the best method of obtaining a higher percentage of germination of C. jamacaru subsp. jamacaru.